APABI conference 2013 ([Institut Bank-Bank Malaysia], 2013)
The current econimic global scenario is perturbed. The debates which took place at the "Waves of Change, Oceans of Opportunities" conference and highlighted in this publication underscores what an exciting time it is to be in the banking and finance industry.